Clozapine-Treatment-Resistant Schizophrenia Successfully Managed with Brexpiprazole Combination Therapy: Two Case Reports. (1st June 2022) - Orsolini, L.; Tempia Valenta, S.; Bellagamba, S.; Salvi, V.; Volpe, U.
Abstract : Introduction: Clozapine has proven to have a unique efficacy on treatment-resistant schizophrenia (TRS). Nevertheless, studies show that 47%-63% of clozapine-treated patients may fail to respond after around 12-years of treatment (CRS). Several augmentation strategies have been proven to be effective in CRS. Objectives: Hereby, we present two clinical cases of CRS successfully managed with brexpiprazole augmentation. Methods: A 48-year-old man without comorbid substance use, treated with clozapine-brexpiprazole augmentation, and a 20-year-old man with comorbid substance use, treated with clozapine-brexpiprazole combination and subsequently with twice-injection aripiprazole (TIA). They were administered with the following assessments at t0, t1-3 (first month), t4-8 (monthly until 6-month follow-up): CGI, BPRS, PANSS, CDSS, Craving VAS, BARS, BIS-11, HRS-A, MADRS, YMRS, AIMS. Results: At 1-month follow-up, both patients showed a considerable improvement (respectively 75% and 55.9% reduction of PANSS total score). At 6-month follow-up, reached only with the first patient, we noticed a further improvement (an overall 37.5% reduction of PANSS total score from the baseline). Conclusions: The present work is the first report describing combination treatment strategies with clozapine and brexpiprazole which appear to give promising results. Disclosure: No significant relationships.